2018
DOI: 10.1055/s-0043-125000
|View full text |Cite
|
Sign up to set email alerts
|

Injuries in Austrian football players: Are they an issue?

Abstract: Lower extremity injuries are the most common injury in Austrian football. The incidence of muscle injuries is high, especially injuries of the posterior thigh. There are promising preventive strategies for the most common injury types. The implementation of these strategies is essential in order to reduce the incidence or recurrence of these football injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In Tables 1 and 2 are inscribed the values of total incidences at training and at matches for professional men football players [4,11,13,14,16,17,19,23, and amateur football players, respectively [19,[25][26][27][28][29][30][62][63][64][65]. In professional football players, thirty-six studies reported the overall incidence, which varied widely from 1.60, 95% confidence interval, injuries/1000 h [37] and 25.6, 95% confidence interval injuries/1000 h of exposure [38].…”
Section: Incidence Of Injuries: General Training and Matchmentioning
confidence: 99%
“…In Tables 1 and 2 are inscribed the values of total incidences at training and at matches for professional men football players [4,11,13,14,16,17,19,23, and amateur football players, respectively [19,[25][26][27][28][29][30][62][63][64][65]. In professional football players, thirty-six studies reported the overall incidence, which varied widely from 1.60, 95% confidence interval, injuries/1000 h [37] and 25.6, 95% confidence interval injuries/1000 h of exposure [38].…”
Section: Incidence Of Injuries: General Training and Matchmentioning
confidence: 99%